Las medidas precautelatorias en el ordenamiento jurídico laboral. - Castro Castro, Oto Manuel (2012)
The prevention rules in the labor matter as: The prohibition, kidnapping, retain and root, to be applied with the condemnation judgment .either it doesn't be executed , ¡t doesn't have the same longed juridlcal effects for the working sort , breaking of this injusted way their constitutional and legal rights partlcularly in their economic, homelike and social aspects. The prevention rules correspond to one of the biggest contribution of the labor right , which is looking to reach a just justice, because they prevent the workers' interests , but according the Work Judgers they are conceded with the judgment, these result ambiguous thaf s why they are ¡nefficient. The negative aspect of this legal disposition is don't apply the prevention rules with initial demand, after that or with given evidence to the process, we must wait for a judgment in order to use them. In this space of time, thaf s it from the acceptation of the demand to the judgment., there will be a lot of situations, because of lack of guaranties in the application of the prevention rules ; situations detected in the practical life, thaf s the case , the employer expand in a not intentional way the process , in order to oblígate to the worker , due his/her economic need , to resign , militating his/her rights; or in other cases, when the employer is considered defeated the judgment . he sells or transfers in fictitious way their properties or he travels to other country avoiding a responsibility, with this he is searching his no good propose, leaving without defense to the humble worker , because the prevention rules as the prohibition , the kidnapping, retain or the root there weren't taken in their opportuníty. Our investigation is oriented to determine with precisión:: a). The Ecuadorian labor legislation, it doesn't have a good processed system for the labor demand ñor only to have e success, it's importaht that this success is assure in favor of who is asking for justice b). The prevention rules don't have a positive effect in the juridical results in the labor matter; c). The actual labor normative with respect to the prevention rules contradict with the constitutional norm respect to the renounce of the workefs rights; and, d). The absence of the fit and effective procedure produces juridical insecurity. In the given dimensions, it is oriented in a clear and objective way the central problem of the investigation.